2021
DOI: 10.1002/aet2.10703
|View full text |Cite
|
Sign up to set email alerts
|

Mastery learning improves simulated central venous catheter insertion by emergency medicine teaching faculty

Abstract: Objectives Routine competency assessments of procedure skills, such as central venous catheter (CVC) insertion, do not occur beyond residency training. Evidence suggests variable, suboptimal attending physician procedure skills. Our study aimed to assess CVC insertion skill by academic emergency physicians, determine whether a simulation‐based mastery learning (SBML) intervention improves performance and investigate for variables that predict competence. Methods This is a pretest–posttest study that evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Studies have shown reduced needle passes, arterial punctures, catheter adjustments, and central line-associated bloodstream infections with SBML training in EM and IM residents. [22,23] Multiple studies have also described previous CVC training curricula, [24][25][26][27] orientation-based CVC curricula, [28][29][30] CVC curricula with SBML principles, [31,32] and an SBML orientation which included paracentesis and lumbar puncture for IM residents and medical students. [33,34] These previous efforts have focused on just-in-time education [22,23,31] or assessment of residents who traditionally performed more procedures during their training.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown reduced needle passes, arterial punctures, catheter adjustments, and central line-associated bloodstream infections with SBML training in EM and IM residents. [22,23] Multiple studies have also described previous CVC training curricula, [24][25][26][27] orientation-based CVC curricula, [28][29][30] CVC curricula with SBML principles, [31,32] and an SBML orientation which included paracentesis and lumbar puncture for IM residents and medical students. [33,34] These previous efforts have focused on just-in-time education [22,23,31] or assessment of residents who traditionally performed more procedures during their training.…”
Section: Discussionmentioning
confidence: 99%
“…Medical simulation is an effective method of practical education: standardized, objective, adjustable, repeatable, safe, and attractive for the students, avoiding risks to patients and learners. Critical life skills can be controlled and adjusted during simulation scenarios, such as: leadership, collaboration, organization, critical thinking, problem-solving skills, independent learning skills, empathy, tolerance, communication skills, teamwork, and accountability [ 63 , 64 ]. It is essential to work with NTS concepts with the medical students since the beginning of the course.…”
Section: Opportunities In Education and Researchmentioning
confidence: 99%